Gender as a Moderator of Descriptive Norms and Substance Use among Latino College Students. (19th September 2018) - Vaughan, Ellen L.; Wright, Lauren A.; Cano, Miguel Ángel; de Dios, Marcel A.
ABSTRACT: This study addresses gaps in the literature by testing gender differences in the associations between substance use norms and substance use among Latino college students. Secondary data analysis was conducted using data from the 2009 National College Health Assessment. Participants selected for this study were 4, 336 Latino undergraduates. Linear mixed modeling was used to test gender as a moderator of the relationship between alcohol use norms and alcohol use as well as marijuana use norms and marijuana use. Results indicated that the strength of the relationships between norms and substance use was stronger for males than for females. Substance use rates and gender roles differ for Latinos and Latinas and may partially account for the stronger relationship between these constructs for males. Implications for future research and prevention are discussed.